Medically Documenting Disability in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) Cases - Comerford, Barbara B.; Podell, Richard (Frontiers in Pediatrics, 2019)
Patients with severe myalgic encephalomyelitis/Chronic fatigue syndrome (ME/CFS) experience debilitating physical and cognitive symptoms, which often result in the need to file disability claims. A significant number of ME/CFS patients are children or adolescents. ME/CFS patients often turn to physicians who are not trained to recognize and diagnose ME/CFS, and who might or might not understand that ME/CFS is a multi-system primarily physical illness. Such misperceptions can adversely affect the doctor-patient relationship, the clinical outcomes, as well as the results of disability claims. According to the National Academies of Science, Engineering and Medicine, “Between 836,000 and 2.5 million Americans suffer from myalgic encephalomyelitis/chronic fatigue syndrome… This disease is characterized by profound fatigue, cognitive dysfunction, sleep abnormalities, autonomic manifestations, pain, and other symptoms that are made worse by exertion of any sort. ME/CFS can severely impair patients' ability to conduct their normal lives.1” The prevalence of MECFS among children and adolescents has been estimated variously as between 0.11 and 4% (1). A large percentage of children and adolescents with ME/CFS suffer from orthostatic intolerance due to one or both of these syndromes: Neurally Mediated Hypotension (NMH) and Postural Orthostatic Tachycardia Syndrome (POTS). These elements of ME/CFS often respond well to proper treatment (2, 3).